2020
DOI: 10.17239/l1esll-2020.20.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Emotions while reading literature in multicultural groups

Abstract: The article presents a qualitative hermeneutic study on literary interpretive interaction in multicultural teachers' groups. Participants were Jewish and Arab teachers in Israel who read a story by Kafka. The objectives of the study were to learn in what ways readers express emotions towards the Other in the text as well as the Others in their learning groups. The activity aimed at generating a literary interpretive discourse and promoting interactive learning involving willingness to face the Other with keen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…This similarity is evident in the practices used by both literature teachers and SBL instructors, whereby their common point of departure is an attitude of curiosity, which leads them to ask questions to which there is no single predefined and correct answer. Through the interpretive discussion that emerges among the learners, which in both cases is focused on the discourse itself (implicitly and explicitly conveyed), the underlying significance is revealed along with the inherent messages, which are meaningful on both the individual and the group level (Elkad-Lehman & Poyas, 2020). In this sense, the findings of the study demonstrated that for literature PSTs, the SBL experience is not only a pedagogical tool but rather an inherent part of their professional discipline, thus creating an essential connection between theory and practice, that is, between the perception of the profession and its learning and teaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This similarity is evident in the practices used by both literature teachers and SBL instructors, whereby their common point of departure is an attitude of curiosity, which leads them to ask questions to which there is no single predefined and correct answer. Through the interpretive discussion that emerges among the learners, which in both cases is focused on the discourse itself (implicitly and explicitly conveyed), the underlying significance is revealed along with the inherent messages, which are meaningful on both the individual and the group level (Elkad-Lehman & Poyas, 2020). In this sense, the findings of the study demonstrated that for literature PSTs, the SBL experience is not only a pedagogical tool but rather an inherent part of their professional discipline, thus creating an essential connection between theory and practice, that is, between the perception of the profession and its learning and teaching.…”
Section: Discussionmentioning
confidence: 99%
“…The very possibility of a dialogue based on awareness of the other creates a polyphony and openness within the literary, sociocultural space (Bakhtin, 1981). A contemporary study that examined preservice literature teachers' interactions with literary fictional characters and with other humans, revealed a variety of ways to consider the textual other, such as by filling in the textual gaps, interpreting symbols, and explicitly examining emotions (Elkad-Lehman & Poyas, 2020). In this sense, literature teaching is based on "narrative empathy," which is defined as follows: " The sharing of feeling and perspective-taking induced by reading, viewing, hearing, or imagining narratives of another's situation and condition" (Keen, 2013, 1).…”
Section: Theoretical Framework 1reading As a Dialogue: Conceptualizat...mentioning
confidence: 99%
“…Israeli society is ethnonationally, religiously and culturally diverse, a diversity mirrored in segregated Arab and Jewish education systems (Levin & Baratz, 2021;Poyas & Elkad-Lehman, 2020). The latter is further subdivided into religious and secular schools.…”
Section: Research Contextmentioning
confidence: 99%
“…In this study, teachers encountered a legend from Jewish sources that they studied in a havruta (study pair) setting, in light of previous studies that pointed to the benefits of havruta learning (see the Method section below) and the approach to the text from a discourse created in peer-group encounters with a text (Elkad-Lehman & Poyas, 2020;Poyas & Elkad-Lehman, 2016).…”
Section: Teaching Texts From Jewish Sourcesmentioning
confidence: 99%